Anatomi Organ Vegetatif Tumbuhan Rija-Rija (Scleria melaleuca) di Kawasan Hutan Kemasyarakatan (HKM) Pusuk Lestari, Lombok Barat - Adinda Emilia Sajida; Baiq Kesy Juliani; Baiq Zulifa Hemidia; Siti Rizki Fitri; R. Muhamad Azis Maulana; Kurniasih Sukenti; Tri Mulyaningsih (Journal of Microbiology, Biotechnology and Conservation, 2025)
Cyperaceae is a plant species that belongs to the sedges family and is characterised by a triangular stem. The sedges plant is frequently observed in rice fields and under the shade of trees, including Scleria melaleuca.The objective of this study is to ascertain the anatomical characteristics of S. melaleuca.The study employed a descriptive exploratory research method and was conducted at the Advanced Biology Laboratory, Faculty of Mathematics and Natural Sciences, University of Mataram. The S. melaleuca plant samples were collected from the Hutan Kemasyarakatan (HKM) Pusuk Lestari Area in Batu Layar, West Lombok Regency, West Nusa Tenggara. The samples included the root organs, stems, leaves and seeds. The samples were preserved in 70% alcohol and sliced using the hand-free section method. The results of the study demonstrated that the S. melaleuca exhibited distinctive characteristics, including the presence of bulliform cells between the leaf epidermis, the presence of both long and short cells, closed concentric vascular bundles in the stems, a triangular stem shape, and amphicribal vascular bundles in the roots.